ETR 300 D’ladybirds house of children / Kelly Anak Unsers... [et.al] - Unsers, Kelly; Mori, Nazatul Fazirah; Talip, Nuryenny; Berandi, Roslind (2011)
The name of our company is D’Ladybirds House of Children. Our business is in the form of a child education which consists of four members. Each partner contributes certain amount of capital as agreed in the partnership agreement. The main business activity is to provide an early education in which the child develops a foundation for a lifetime of creative learning. All members are entitled to participate in the business management. We have reached an agreement to entitle that Miss Nazatul Fazirah Binti Mori will act as our General Manager and she also act Operation Manager, Miss Nuryenny Binti Hj. Talip as the Administrative Manager, Madam Kelly ak Unsers acts as the Financial Manager and Madam Roslind ak Berandi as the Marketing Manager. The selection of the General Manager is based upon the consensus among the partners and is selected based on the experience, skills and ability.The management team will be headed by the General Manager and assisted by the other managers. The General Manager is responsible in planning, leading, controlling and organizing the business. The Administration Manager is responsible for all administrative jobs such as planning and arranging the remuneration schedule of salaries and wages. The Operation Manager is responsible for the operation and will be supervising and coordinating the operation of the business. The Financial Manager will handle all financial matters such as preparing the budget and financial statements for the expenses of each departments and controlling the money flow of the organization. Lastly, the Marketing Manager will be responsible to create the marketing plan, identifying customers’ needs and demands, identifying the competitors, the target market and the market size and forecasting the future market.